Food is the Asian Way of Showing Love: a Semiotic Analysis - Rizkhi Dinda Pratiwi; Umi Marfathonah (JSSH (Jurnal Sains Sosial dan Humaniora), 2023)
This study aims to figure out the signs behind the "Let's Eat" animation film regarding food to show love in the Asian community and the symbol of love in the "Let's Eat" animation film. This qualitative study uses Roland Barthes' semiotic theory to analyze the data. The results show that the sentiment of food as a symbol of love in Asian culture is deeply rooted in the historical famine. Food as a symbol transforms from a means to survive to a casual way of showing love. This ideology of love is well-represented in the film, which concludes with five main points of implied meaning.